SARS-CoV-2 infection in pediatric population - Manti, Sara; Licari, Amelia; Montagna, Lorenza; Votto, Martina; Leonardi, Salvatore; Brambilla, Ilaria; Castagnoli, Riccardo; Foiadelli, Thomas; Marseglia, Gian Luigi; Cardinale, Fabio; Caffarelli, Carlo; Tosca, Maria Angela; et al. (Acta Biomedica Atenei Parmensis, 2020)
n December 2019, in Wuhan (Hubei, China), the first COVID-19 cases due to SARS-COV-2 had been reported. On July 1st 2020, more than 10.268.839 million people had developed the disease, with at least 506.064 deaths. At present, Italy is the third country considering the number of cases (n=240.760), after Spain, and the second for the cumulative number of deaths (n=249.271), after the United States. As regard pediatric COVID-19 cases, more than 4000 cases (have been reported; however, these figures are likely to be underestimated since they are influenced by the number of diagnostic tests carried out. Three pediatric deaths have been reported in Italy to date. We aimed to review the peculiar aspects of SARS-COV-2 infection in the pediatric population.